An age of infidels : the politics of religious controversy in the early United States - Schlereth, Eric R. (Philadelphia : University of Pennsylvania Press, 2013)
"Historian Eric R. Schlereth places religious conflict at the center of early American political culture. He shows ordinary Americans--both faithful believers and Christianity's staunchest critics--struggling with questions about the meaning of tolerance and the limits of religious freedom. In doing so, he casts new light on the ways Americans reconciled their varied religious beliefs with political change at a formative moment in the nation's cultural life. After the American Revolution, citizens of the new nation felt no guarantee that they would avoid the mire of religious and political conflict that had gripped much of Europe for three centuries. Debates thus erupted in the new United States about how or even if long-standing religious beliefs, institutions, and traditions could be accommodated within a new republican political order that encouraged suspicion of inherited traditions. Public life in the period included contentious arguments over the best way to ensure a compatible relationship between diverse religious beliefs and the nation's recent political developments. In the process, religion and politics in the early United States were remade to fit each other. From the 1770s onward, Americans created a political rather than legal boundary between acceptable and unacceptable religious expression, one defined in reference to infidelity. Conflicts occurred most commonly between deists and their opponents who perceived deists' anti-Christian opinions as increasingly influential in American culture and politics. Exploring these controversies, Schlereth explains how Americans navigated questions of religious truth and difference in an age of emerging religious liberty."--Publisher's description.
Introduction : Remaking religion -- 1. Boundaries -- 2. America's Deist future -- 3. Citizen Deists -- 4. Partisan religious truths -- 5. America's Deist past -- 6. Free enquiry -- 7. Political religion, political irreligion -- Epilogue : The origins of American cultural politics.
Based on the author's thesis from Brandeis Univ., 2008.
Includes bibliographical references (pages 243-282) and index.
Keywords: Christianity and politics -- United States -- History; Christianity and culture -- United States -- History; Christianity and other religions -- United States; Church and state -- United States -- History; Deism -- United States -- History; United States -- Politics and government -- 1783-1865.; Christianity and culture; Christianity and other religions; Christianity and politics; Church and state; Deism; Political science; United States; Religionspolitik; Kirche; Staat; Glaubensfreiheit; USA; Christianisme et politique -- x; Christianisme et culture -- x; z -- Histoire; z -- Histoire; x; 1783 - 1865; History